KAJIAN KESESUAIAN PENYIMPANAN SEDIAAN OBAT DAN ANALISIS SISTEM PENYIMPANAN OBAT GUDANG FARMASI DI DAERAH BALI TIMUR TAHUN 2022 - Swastini, Ni Luh; Septiari , I Gusti Ayu Agung Septiari; Mayun , I Gusti Ngurah (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2023)
Inappropriate medicine storage can cause the stored medicines to suffer losses in the preparation product which will result in damage to the medicine before the expired date. To avoid damage in drug storage, it is necessary to conduct a good storage and practice medicine storage system analysis. This study aims to analyze the medicine storage system and the suitability of medicine storage in the East Bali Regional Pharmacy Warehouse against the regulations of the Ministry of Health of the Republic of Indonesia in 2007. This research is a descriptive study using qualitative data. Sampling is based on total technique sampling. The types of data used in this research are primary data and secondary data. Primary data was obtained from direct observation and interviews, secondary data was obtained from medicine storage data for 2022. The results of the study showed the suitability of storing medicine preparations in the East Bali District Pharmacy Warehouse against the regulations of the Ministry of Health of the Republic of Indonesia in 2007, indicating that all indicators were following the regulations of the Ministry of Health of the Republic of Indonesia in 2007, based on research results showing that they were categorized in the very good to good category.The medicine storage system at the East Bali District Pharmacy Warehouse against standards shows that all indicators were in accordance with the standars.